INVENTARISASI SERANGGA DAN TINGKAT KERUSAKAN YANG DITIMBULKAN PADA TEGAKAN JATI (Tectona grandis LINN.F) DI AREAL HUTAN TANAMAN RAKYAT (HTR) NEGERI HILA KABUPATEN MALUKU TENGAH - Cornelia M A Wattimena; Fransina Sarah Latumahina; Noor Khomsah Kartikawati (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2020)
The study aims to determine the types of insects that attack teak plants, diagnose the symptoms of attack and estimate the magnitude and intensity of attacks caused by teak pest attacks. The results found two types of pests that attack teak stands namely Woodhoppers (Valanga nigricornis) and Caterpillars (Hyblaea puera) with moderate damage intensity. Wooden Grasshopper (Valanga nigricornis) measuring 45 - 55 mm (male) and 1575 mm (female), has a head, chest, thorax and abdomen, yellowish brown with a dark blue hue on the wings. The rear wing is visible when flying and is red. Teak caterpillars (Hyblaea puera) are found to be brown with a pair of small yellow stripes on each side, and between two lines are dark brown with a length of 3.5 cm, while the cocoon is dark brownish black, with an average length of 1.4-1, 9 cm, and an average weight of 0.7-1.3 mg. Valanga nigricornis attack area of 29.58% belong to the category of moderate attack and Hyblaea puera of 23.41% belonging to the category of mild attack